The Role of Teaching Factory Learning on Entrepreneurial Readiness of Students of Visual Communication Design Competency SMKN 1 Tasikmalaya - Irma Suryaningsih; Azizah Fauziyah; Ismail Yusup (Edumaspul: Jurnal Pendidikan, 2024)
Entrepreneurship has a very important role in overcoming the problem of unemployment because, through entrepreneurship, a person can create and provide new jobs. The birth of an entrepreneur is motivated by entrepreneurial readiness or there is a feeling of readiness equipped with the ability, willingness, and desire to face various situations and conditions in entrepreneurship. The purpose of this study is to identify the effect of Teaching Factory learning on student entrepreneurial readiness in Visual Communication Design competency of SMKN 1 Tasikmalaya. This study involved a population of 93 students in grade XI of the competency. Determination of the sample in this study is using purposive sampling technique or sampling with certain considerations. The sample of this study consisted of 34 students who were taking Teaching Factory learning. The data collection technique in this study was through interviews and distributing questionnaires via Google Forms. Simple linear regression analysis was used to analyze the data. The results of this study indicate that teaching factory learning has an effect of 47.7% on the entrepreneurial readiness of visual communication design competency students of SMKN 1 Tasikmalaya.